Spectrum of Corpus Callosum Agenesis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Magnetic resonance imaging and clinical features of 16 children with agenesis of the corpus callosum (ACC) are reviewed at UAE University, United Arab Emirates.